New Report of Endophytic Sordariomycetes from the Seagrasses of Cebu, Central Philippines: Endophytic Sordariomycetes from Philippine seagrasses - Kinamot, Venus Bantoto; Monotilla, Alvin (Journal of Tropical Life Science, 2023)
Sordariomycete is one of the dominant components of the endophytic community in seagrasses. However, there are still many species under this group that still need to be described. Among the tropical seagrasses, the Philippines had the least number of endophytic Sordariomycete reported. This study reports the isolation of endophytic Sordariomycete from Enhalus acoroides, Cymodocea serrulata, and Thalassia hemprichii. Seagrass samples were collected from the coastal areas of Hilutungan Channel, Cebu, Central Philippines using a sterilized razor. Explants from seagrass samples were surface-sterilized, inoculated in culture plates, and incubated for 14 days at 27±2°C. Fungi that grew from the edge of explants were purified and identified through morphological and molecular methods using ITS sequences. Molecular phylogeny was inferred by neighbor-joining with 1000 bootstrap replications. Three species of Sordariomycete were identified in this study. Fungal isolates from the rhizomes and roots of Cymodocea serrulata had 99.84% nucleotide similarity with Eutypella sp. Isolates from the rhizomes and roots of Enhalus acoroides had a 100% match identity with Beauveria bassiana. While the isolate from the leaf of Thalassia hemprichii had a 99% nucleotide affinity to Xylaria apoda. These isolates formed a well-supported clade with their closest match taxa at 100% bootstrap support. The estimate of evolutionary divergence between the isolates’ sequences and their reference taxa was 0.0, suggesting no nucleotide base substitutions per site. The identification of seagrass isolates as Eutypella sp., Beauveria bassiana, and Xylaria apoda is hereby supported. Phylogenetic analysis revealed that endophytic fungi from the Philippine seagrass did not cluster with any fungal species previously reported from the Philippines, suggesting different species. To our knowledge, Eutypella sp., Beauveria bassiana, and Xylaria apoda were the first reports of endophytic Sordariomycete in Philippine seagrasses. The isolation of these endophytes is promising because these genera are a rich source of novel compounds and biocontrol agents.